Detailed Studies of Radiogalaxy Mrk1032 - Hakopian, S. A.; Dodonov, S. N.; Andreasyan, R. R.
The first results of the observations of Mrk1032, conducted with the 6-m telescope of SAO Russia, are given. It is shown, in particular, that a large complex of HII-regions, revealed by the integral-field spetroscopy, is the main source of UV radiation in the galaxy.
Keywords: Astronomy